Evaluation of Active Labour Market Policy: Methodological Concepts and Empirical Estimates - Reinhard Hujer; Marco Caliendo (Institute for the Study of Labor (IZA), 2000)
Persistently high unemployment, tight government budgets and the growing scepticism regarding the effects of active labour market policies (ALMP) are the basis for a growing interest in evaluating these measures. This paper intends to explain the need for evaluation on the micro- and macroeconomic level, introduce the fundamental evaluation problem and solutions to it, give an overview of the newer developments in evaluation literature and finally take a look on empirical estimations of ALMP effects.
Keywords: H43; J64; C14; J68; C33; 330; Active labour market policy; evaluation; matching; difference-in-differences; Arbeitsmarktpolitik; Wirtschaftspolitische Wirkungsanalyse; Wissenschaftliche Methode; Ökonometrie; Theorie; Deutschland